Peripartum and neonatal outcomes of small‐for‐gestational‐age infants with gastroschisis. (May 2015) - Girsen, Anna I.; Do, Samantha; Davis, Alexis S.; Hintz, Susan R.; Desai, Arti K.; Mansour, Trina; Merritt, T. Allen; Oshiro, Bryan T.; El‐Sayed, Yasser Y.; Blumenfeld, Yair J.
Abstract Objectives Neonates with gastroschisis are often small for gestational age (SGA) based on population nomograms. Our objective was to evaluate the effect of SGA on perinatal and neonatal outcomes in cases of gastroschisis. Methods This is a retrospective study of neonates with prenatally diagnosed gastroschisis from two academic centers between 2008 and 13. Perinatal and neonatal outcomes of neonates with SGA at birth were compared with appropriate‐for‐gestational‐age (AGA) neonates. The primary composite outcome was defined as any of the following: neonatal sepsis, short bowel syndrome at discharge, prolonged mechanical ventilation (upper quartile for the cohort), bowel atresia or death. Results We identified 112 cases of gastroschisis, 25 of whom (22%) were SGA at birth. There were no differences in adverse peripartum outcomes between SGA and AGA infants. No difference was found in the primary composite neonatal outcome (52% vs 36%, p = 0.21), but SGA infants were more likely to have prolonged mechanical ventilation (44% vs 22%, p = 0.04) and prolonged length of stay (LOS) (52% vs 22%, p = 0.007). After adjusting for GA at delivery, SGA remained associated with prolonged LOS (OR = 4.3, CI: 1.6–11.8). Conclusion Among infants with gastroschisis, SGA at birth is associated with a fourfold increase in odds for prolonged LOS, independent of GA. © 2015 John Wiley & Sons, Ltd.